A Development of Personal Coaching Mobile Application: Coach Me - Anuar, Bassiman; Mohd Yusof, Munirah (Applied Information Technology And Computer Science, 2023)
With number of closing gymnasiums increasing exponentially, it entails the steady decline of unemployment in the fitness industry particularly amongst the fitness coaches or instructors. Thus, personal trainers and coaches do not have a dedicated platform during the pandemic to train students from home due to the COVID-19 Pandemic. Hence, this project aims to design, develop, and test a personal coaching mobile application called Coach Me by using the incremental prototyping as the software methodology to tackle these problems. The mobile application will be built using Flutter, a Dart framework, Node.js runtime environment and MySQL database. The significance of this project is that the mobile application boosts the camaraderie between trainers and their students even with the physical limitation of not being able to enter a gym providing a platform for both parties to connect. Albeit if the pandemic has reached its endpoint, the mobile application will not lose its traction and continue to thrive as it will drive coaches and students who are not able to attend a physical class in using the mobile application as a platform to professionally connect and re-watch video lessons.